Thermonuclear power plant model - Esteves, João Sena (2007)
This paper describes a model of a thermonuclear power plant with a very detailed electrical substation. The model includes facilities such as an operational railroad, a train shed, a container crane and two diesel oil filling stations. The result is very eye-catching and most suitable for the classroom or science-fair events. A brief technical explanation on the components of real-world nuclear power plants and electrical substations is also given.